Produção de compostos antimicrobianos por Paenibacillus polymyxa RNC-D: otimização das condições de cultivo, purificação e caracterização dos bioprodutos - Serrano, Nadja Fernanda Gonzaga (2014)
The increase in the production of antimicrobial metabolites by Paenibacillus polymyxa RNC-D was appraised through the study of cultivation variables. Two process variables, namely the glucose and inoculum concentrations, were evaluated in different levels (5 to 40 g/l, and 2.5% to 5.0% v/v, respectively), and their effects on biomass formation, minimal inhibitory concentration (MIC) against Escherichia coli and surface tension reduction (STR) were studied. The fermentation process was firstly carried out using non-optimized parameters, where the dependent variables biomass, MIC and STR reached the values of 0.6 g/l, 1.000,0 μg/ml and 18.4 mN/m, respectively. The optimum glucose (16 g/l) and inoculum concentrations (5.0% v/v) were defined in order to maximize the biomass formation, with low value of MIC and large STR of extract. Under these conditions, a biomass of 2.76 g/l, MIC of 15.8 μg/ml, and STR of 14.58 mN/m were predicted by the model. Data attained by experiments using optimized settings showed the following values: biomass 2.05 g/l; MIC 31.2 μg/ml; STR 10.7 mN/m. Thus, the percentage of improvement for each target response was: biomass 241.6%; MIC 96.88%; STR 41.85%. It was found that high concentrations of glucose substrate, although reflected in an increase in bacterial biomass, inhibited the microbial secondary metabolism, resulting in a low production of biomolecules associated with high values of MICs. Thus, initial concentrations of glucose and inoculum are shown as variables of strong influence in the production of antimicrobial metabolites by P. polymyxa RNC-D. Through the methods of experimental factorial design and surfaceresponse followed by graphical optimization it was possible to determine the optimum operating condition to achieve both maximum biomass and RTS as well as and lowest possible values of CIM. The validity of the proposed model was verified and confirmed. This is the first study on the optimization of culture conditions for the production of antimicrobial metabolites by P. polymyxa RNC-D, and constitutes an important step in the development of strategies to modulate the production of antimicrobial molecules by this microorganism in elevated levels. Novel antimicrobial compounds were isolated from the fermentation broth of P. polymyxa RNC-D, here named total extract (TE). It was possible to verify the presence of lipopeptide and peptide active compounds through enzymatic assays made with ET. Total extract was subjected to a two-phase system, resulting in lipopeptide extract (LPE) and aqueous fraction (AF). According to the results of bioassays, LPE has broad-spectrum activity against Gram-positive bacteria, Gram-negative bacteria and fungi. The mass spectrometry analysis of PLA revealed the existence of a novel compound that was named polycerradin. The purification of a novel antimicrobial peptide (AMP) from the AF was carried out by using chromatography. The compound was active against Gram-negative bacteria. Nterminal analysis determined the amino acid sequence, as well as MS / MS analysis confirmed the primary structure of this new compound. This research reports firstly the production of PAM PpRNCD that has an unusual amino acid in its constitution. It is an unprecedented fact considering the bacterial specie P. polymyxa. In terms of molecule size, PAM PpRNCD can be considered one of the smallest active natural peptide reported to date. It was also possible to isolate from FA the depsipeptides IL-F04a (m/z 883), LI-F04b (m/z 897), LI-F03a (m/z 947) and LI-F03b (m/z 961) previously described in the literature. The photoluminescence study of the LPE, TE, AF in both at room temperature (RT) and low temperature (T = 8K) was performed. In addition, this technique was applied to evaluate the action of the ELP on Staphylococcus aureus ATCC 29213, Enterococcus faecalis ATCC 29212, Escherichia coli ATCC 29212, Shigella sonnei ATCC 1578 and Candida albicans ATCC 10231 in two different situations: (a) immediately after mixing LPE with the bacterial and fungus cell suspension, and (b) after thirty minutes. The photoluminescence emission was collected by a triple spectrometer (three diffraction gratings) T64000 model from Jobin Yvon, equipped with an optical microscope. For the detection of the radiation emitted by the sample we used a CCD camera (charge coupled device) cooled by liquid nitrogen. The slits of the spectrometer were adjusted to produce a spectral resolution of the order of 10-4 nm. The excitation source used was the line of 457 nm (violet) from an argon laser. The behaviors here observed indicate a strong potential for applications in biosensors as well as molecular markers.